CHALLENGES OF TRANSLATING LEGAL DOCUMENTS:THE DILEMMA OF TERMINOLOGY AND FUNCTIONAL EQUIVALENCE (Ustozlar uchun, 2026)
This article explores the intricate challenges inherent in legal translation, focusing primarily on the conflict between rigid terminology and the search for functional equivalence. Legal systems are deeply rooted in specific national cultures and histories, making the transfer of concepts between disparate jurisdictions (e.g., Common Law vs. Civil Law) exceptionally complex. The study examines why literal translation often fails in a legal context and argues for a communicative approach that prioritizes legal effect over linguistic symmetry.